Pemberdayaan Perempuan Nelayan Bale Bungo (Oxyeleotriks Marmorata) sebagai Upaya Pengembangan Usaha Produk Oleh-Oleh Khas Wajo - An Ras Try Astuti (LP2M of Institute for Research and Community Services - UIN Walisongo, 2020)
This research aims to design an empowerment model that is appropriate to the character of the community in Wajo, South Sulawesi. The focus of this research-based empowerment activity is the development of the business of women fisherman Bale Bungo (oxyeleotris marmorata). This study uses a qualitative approach model with a participatory action research (PAR) method. The research subjects consisted of the head of the sub-district, the village head and the fisherman Women's Community. The data of this study were obtained by observation, interview and documentation techniques. The results of the study are as follows. (1) Identification of community needs through Brainstorming (2) Mapping of Village Potential (3) Planning and increasing the capacity of group members through a series of training and focus group discussions (FGD). Indicators of successful training include increasing knowledge and skills to process Bungo into value-added souvenirs. Fisherman women, as well as the increasing economic income of the surrounding community. In addition, it is expected that in the future there will be a Sustainability of women's empowerment program in developing business products in order to compete and compete at the national and international levels. Penelitian ini bertujuan untuk mendesain model pemberdayaan yang sesuai dengan karakter masyarakat di Kabupaten Wajo, Sulawesi Selatan. Fokus pada kegiatan pemberdayaan berbasis penelitian ini adalah pengembangan usaha perempuan nelayan Bale Bungo (oxyeleotris marmorata) Penelitian ini menggunakan model pendekatan kualitatif dengan metode participatory action research (PAR).Subjek penelitian terdiri dari kepala kecamatan dan Komunitas Perempuan nelayan. Data penelitian ini diperoleh dengan teknik observasi, wawancara, dan dokumentasi. Hasil penelitian adalah sebagai berikut. (1) Identifikasi kebutuhan masyarakat melalui Brainstorming (2) Pemetaan Potensi (3) Perencanaan dan melakukan peningkatan kapasitas anggota kelompok Melalui serangkaian pelatihan dan focus group discussion (FGD). Indikator keberhasilan pelatihan diantaranya adalah bertambahnya pengetahuan dan keterampilan untuk mengolah ikan bungo menjadi produk oleh-oleh yang bernilai tambah ekonomis. Perempuan nelayan, serta meningkatnya pendapatan ekonomi masyarakat sekitar. Selain itu, diharapkan kedepannya akan ada Keberlanjutan program pemberdayaan perempuan dalam pengembangan produk usaha agar dapat bersaing dan berkompetisi ditingkat nasional dan international